2018
DOI: 10.1002/jrs.5366
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of the photosensitive pigment Prussian blue

Abstract: Prussian blue is a pigment highly sensitive to electromagnetic radiation, visible light included. This photosensitivity, associated with a complex redox behavior, causes a vulnerability even to Raman lasers, with the possibility of sample alteration or irreversible damage. In this study, we systematically explored the influence of the laser wavelength and laser power on different types of Prussian blue pigments, soluble and insoluble. The use of different laser wavelengths does not influence the position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 23 publications
4
67
0
2
Order By: Relevance
“…Finally, the blue trace signifies the Ti 3 C 2 T x /PB composite. Typical signatures of Ti 3 C 2 T x are observed at 204, 376, and 578 cm −1 , and signatures of PB at around 272, 2,092, and 2,155 cm −1 , which further confirmed the successful synthesis of Ti 3 C 2 T x /PB composites . As indicated from the AFM measurements (Figure S8, Supporting Information), the Ti 3 C 2 T x nanosheet has a uniform thickness of 1.8 nm, which includes trapped water molecules between the flake and the substrate .…”
Section: Resultssupporting
confidence: 63%
“…Finally, the blue trace signifies the Ti 3 C 2 T x /PB composite. Typical signatures of Ti 3 C 2 T x are observed at 204, 376, and 578 cm −1 , and signatures of PB at around 272, 2,092, and 2,155 cm −1 , which further confirmed the successful synthesis of Ti 3 C 2 T x /PB composites . As indicated from the AFM measurements (Figure S8, Supporting Information), the Ti 3 C 2 T x nanosheet has a uniform thickness of 1.8 nm, which includes trapped water molecules between the flake and the substrate .…”
Section: Resultssupporting
confidence: 63%
“…Bands located in the spectral window between 450-620 cm -1 are characteristic of all Fe-C stretching vibrations [24] and manifest in the spectrum at 523 cm -1 . The lower spectral region (190-340 cm -1 ) with bands at 277 cm -1 and 328 cm -1 concern the Fe-CN-Fe bond deformation vibrations [24].…”
Section: Blue Colormentioning
confidence: 99%
“…The µ-Raman spectrum allowed the clear identification of the Prussian blue pigment, Figure 4B, displaying the characteristic stretching vibrations of the triple CN bond at 2070-2200 cm −1 [24], which is visible in the spectrum at 2152 cm −1 and 2090 cm −1 . Bands located in the spectral window between 450-620 cm −1 are characteristic of all Fe-C stretching vibrations [24] and manifest in the spectrum at 523 cm −1 . The lower spectral region (190-340 cm −1 ) with bands at 277 cm −1 and 328 cm −1 concern the Fe-CN-Fe bond deformation vibrations [24].…”
Section: Blue Colormentioning
confidence: 99%
“…Moretti and Gervais studied the photosensitive pigment Prussian blue using Raman spectroscopy. They systematically explored the influence of the laser wavelength and laser power on different types of Prussian blue pigments, soluble and insolulble, and found that use of different laser wavelengths does not influence the positions of the characteristic peaks, though it affects the signal‐to‐noise ratio . Pagliai and co‐workers carried out DFT calculations of the IR and Raman spectra of anthraquinone dyes and lakes.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…They systematically explored the influence of the laser wavelength and laser power on different types of Prussian blue pigments, soluble and insolulble, and found that use of different laser wavelengths does not influence the positions of the characteristic peaks, though it affects the signal-to-noise ratio. [135] Pagliai and coworkers carried out DFT calculations of the IR and Raman spectra of anthraquinone dyes and lakes. The computed vibrational frequencies have been adopted as a guideline to propose the vibrational assignment of the dyes and to obtain useful information on the Raman spectra of their aluminium complexes.…”
Section: Time-resolved and Ultrafast Raman Spectroscopymentioning
confidence: 99%